2022
DOI: 10.3389/fnbeh.2022.1038981
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal oscillations: early biomarkers of psychiatric disease?

Abstract: Our understanding of the environmental and genetic factors contributing to the wide spectrum of neuropsychiatric disorders has significantly increased in recent years. Impairment of neuronal network activity during early development has been suggested as a contributor to the emergence of neuropsychiatric pathologies later in life. Still, the neurobiological substrates underlying these disorders remain yet to be fully understood and the lack of biomarkers for early diagnosis has impeded research into curative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…Indeed, we recently demonstrated that transient inhibition of OB outputs at the start of the second postnatal week in mice reduces coordinated activity in the hippocampal formation and impairs cognitive abilities later in life [23]. These findings resemble the developmental deficits observed in mouse models of neuropsychiatric disorders [24,25]. Accumulating evidence suggests an association of olfactory impairment with neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Indeed, we recently demonstrated that transient inhibition of OB outputs at the start of the second postnatal week in mice reduces coordinated activity in the hippocampal formation and impairs cognitive abilities later in life [23]. These findings resemble the developmental deficits observed in mouse models of neuropsychiatric disorders [24,25]. Accumulating evidence suggests an association of olfactory impairment with neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 75%
“…Both, WT and GE mice showed continuous activity in the local field potential (LFP) recorded in the OB with the typical dominant respiration rhythm (RR, 2-4 Hz) that reverses polarity at the MCL (Fig 2C). However, the power in RR and theta (4-12 Hz) frequency bands were significantly reduced in GE mice (RR p=5.1x10 -4 , theta p=0.004), whereas the power in beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) was not significantly different (p=0.09) (Fig 2D). Further, the firing rate of single units in the OB was reduced in GE mice, particularly for neurons in the MCL (MCL p=0.023; GCL p=0.51), indicating a reduction in the activity of OB projection neurons in the absence of odor stimulation (Fig 2E).…”
Section: Reduced Ob Activity In Immune-challenged Disc1 +/Mice During...mentioning
confidence: 91%
See 1 more Smart Citation
“…Neural oscillations are involved in various cognitive functions, such as memory, attention, and decision making, and are modulated by various factors, such as sensory input, task demands, and emotional states [160][161][162][163]. Neural oscillations are also affected by neuropsychiatric disorders, including SCZ, BD, and autism, and may serve as biomarkers or targets for diagnosis and intervention [164][165][166][167]. In this subsection, we review two papers that explore the role of alpha oscillations, a type of brain wave that occurs in the range of 8-12 Hz, in various cognitive functions, and how they are affected by neuropsychiatric disorders.…”
Section: Neural Oscillations and Cognitive Functionsmentioning
confidence: 99%
“…These oscillations are a key indicator of the communication status between neurons that together form circuits that collectively make up neural networks. In our search to understand the mechanisms that underlie behavior or cognition, and in our pursuit of novel biomarkers of disorder pathology, researchers have long assessed how circuit/network function alterations may contribute to neurological disorder manifestation ( 3 , 4 ). Unfortunately, we have not been as successful as hoped, with inconsistencies in many of the findings.…”
mentioning
confidence: 99%